DUKUNGAN PSIKOSOSIAL MELALUI LAYANAN BIMBINGAN DAN KONSELING KOMUNITAS PADA ANAK BERKEBUTUHAN KHUSUS (ABK) - Ikrimania Mosleh; Azlena Vira Safitri; Ulfa Madina Fitrayani; Natalia Pare; Denok Setiawati; Najlatun Naqiyah (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
Children with Special Needs often face challenges in social interaction, emotional adjustment, and environmental acceptance. Psychosocial support is a crucial factor in helping them achieve optimal development. This study aims to explore the psychosocial support provided through community guidance and counseling services in Sebaya Sidoarjo. The method used is a qualitative approach with a case study, involving in-depth interviews, observations, and documentation. The results indicate that these services provide emotional support, social skills development, and collaboration with parents. However, challenges such as social stigma and resource limitations still exist. This research emphasizes the importance of collaboration among teachers, parents, and the community to create an environment that supports the development of Children with Special Needs. The findings provide insights for the development of policies and best practices in guidance and counseling services for Children with Special Needs in Indonesia.